A survey of time management and particular tasks undertaken by consultant microbiologists in the UK. Issue 5 (19th May 2006) - Riordan, Terry; Cartwright, Keith; Cunningham, Richard; Logan, Margaret; Wright, Paul
Abstract : Background: Medical microbiology practice encompasses a diverse range of activities. Consultant medical microbiologists (CMMs) attribute widely differing priorities to, and spend differing proportions of time on various components of the job. Aim: To obtain a professional consensus on what are high-priority and low-priority activities, and to identify the time spent on low-priority activities. Method: National survey. Results: Many respondents felt that time spent on report authorisation and telephoning of results was excessive, whereas time spent on ward-based work was inadequate. Timesaving could also be achieved through better prioritisation of infection-control activities. Conclusion: CMMs should apportion their time at work focusing on high-priority activities identified through professional consensus.